Labour absorption and growth in agriculture China and Japan / by Shigeru Ishikawa, Saburo Yamada and S. Hirasima - Ishikawa, Shigeru (Bankok, 1982)
This book presents in one volume the results of further work carried out by the ARTEP on the experience of labour absorption in East Asian agriculture, focussing on the contemporary experience of China and the historical experience of Japan. The papers were prepared within the frame work of a major project on "Labour Absorption in Asian Agriculture" which was initiated in 1978 with the objective of generating a knowledge base that would help in formulating policies for greater productive employ ment generation in the developing Asian countries. One of the central con cerns of the project was to examine comprehensively the historical and contemporary experience of some East Asian countries in successfully ex panding both employment and output in agriculture. A careful review of this experience was considered to be of crucial importance in the attempts towards finding ways of productively absorbing more labour in agriculture of the South and Southeast Asian countries, many of which are faced with serious problems of rural unemployment and low productivity. Since the initiation of the project the ARTEP has so far completed a number of studies on the East Asian experience as well as studies on the level of labour input and output in agriculture of several South and Southeast Asian countries. It is hoped that the present set of studies will contribute to widen our knowledge on the East Asian experience and stimulate further discus sion on the subject.
Keywords: Agricultural labourers China